2013
DOI: 10.1002/ajim.22266
|View full text |Cite
|
Sign up to set email alerts
|

Opioid poisonings and opioid adverse effects in workers in Washington State

Abstract: Many poisonings and adverse effects occurred in patients without high dose or long-term opioid therapy, suggesting that opioid dosing and duration guidelines may not be sufficient to reduce morbidity related to prescription opioid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Therefore, given differing potency of long-acting oxycodone, there is potential for dosing errors that could lead to accidental opioid overdoses. Lastly, this increase may be related to the increasing prevalence of high-dose opioid use, which aligns with findings following the release to the Washington State guidelines [24], and suggests that guidelines and legislation alone may not be sufficient to reduce opioid-related toxicity, particularly in an environment of increasing prevalence of high-dose opioid use…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, given differing potency of long-acting oxycodone, there is potential for dosing errors that could lead to accidental opioid overdoses. Lastly, this increase may be related to the increasing prevalence of high-dose opioid use, which aligns with findings following the release to the Washington State guidelines [24], and suggests that guidelines and legislation alone may not be sufficient to reduce opioid-related toxicity, particularly in an environment of increasing prevalence of high-dose opioid use…”
Section: Discussionmentioning
confidence: 62%
“…68 Similarly, in a workers' compensation system, most opioid overdoses occurred in patients who were not receiving high dose or long term opioids. 94 Thus, efforts to reduce overdose risks may need to extend to all patients receiving prescription opioids.…”
Section: Urine Drug Screensmentioning
confidence: 99%
“…The use of prescription opioids is a growing concern in North America [Furlan et al, ; MMWR ]. Prescription opioids have been associated with increased mortality and morbidity in the general [Calcaterra et al, ; Cerda et al, ] and Workers Compensation Board (WCB) populations [Franklin et al, ; Fulton‐Kehoe et al, ]. We have recently shown that a WCB claimant population is more likely to be prescribed higher doses of opioids and that these drugs are prescribed for longer durations than population based controls [Kraut et al, ].…”
Section: Introductionmentioning
confidence: 99%